The amazing spider-man (2014), volume 4 ebook Graveyard shift - special. - Gage, Christos (The Amazing Spider-Man (2014),, 2015)
Collects Amazing Spider-Man (2014) #16-18, Amazing Spider-Man Annual (2014) #1. The cross-dimensional craziness of Spider-Verse is over, and Peter Parker has returned home, but that doesn't mean Spider-Man is safe — not even at his own company! Parker Industries' security systems can keep out any living thing — but what about a Ghost? That's right, the infamous super-powered saboteur has invaded Parker Industries and is targeting its staff! But why? One thing is certain: No secret is safe from the Ghost — and no person is safe, either! A huge chapter in the Amazing Spider-Man's history comes to a close right here, as Peter's choices as CEO of Parker Industries come home to roost! Plus: two special Spider-Man stories by Marvel's newest rising stars that will have everyone talking — and a fan-favorite supporting character takes a turn in the spotlight!